Facile fabrication of fully biodegradable and biorenewable poly (lactic acid)/poly (butylene adipate-co-terephthalate) in-situ nanofibrillar composites with high strength, good toughness and excellent heat resistance. (January 2020) - Liu, Tong; Lian, Xinghan; Li, Lengwan; Peng, Xiangfang; Kuang, Tairong
Abstract: Fully biodegradable and renewable polymer materials have shown broad application prospects with minimal environmental degradation. In the current study, eco-friendly poly(lactic acid)/poly(butylene adipate-co-terephthalate) (PLA/PBAT) in-situ nanofibrillar composites with hierarchical crystal architectures, high mechanical performance and excellent heat resistance properties were fabricated using the loop oscillating push-pull molding (LOPPM) technique and in-situ PBAT nanofibrils were used to induce highly oriented hybrid shish-kebabs. Benefiting from the flow-induced crystallization and abundant hybrid shish-kebabs, the overall crystallinity of LOPPM-processed PLA/10 wt%PBAT sample increased by 4-fold than the conventional injection-molded (CIM) neat PLA sample. The present work indicated that the tensile strength, Young's modulus, elongation at break and impact strength of LOPPM-processed PLA/10 wt%PBAT were higher than the CIM-processed PLA by 36.2%, 12.5%, 181.8% and 253.7%, respectively. The vicat softening temperature was elevated from 59.6 °C to 104.8 °C, and the thermostability also enhanced due to the construction of hybrid shish-kebabs. Strong, tough and heat-resistant PLA/PBAT in situ nanofibrillar composites exhibited outstanding properties for use under more demanding circumstances and are environmentally friendly. Highlights: High performance PLA/PBAT in-situ nanofibrillar composites were prepared by means of LOPPM technique. The intense oscillating shear flow field improved the interfacial adhesion of the immiscible PLA and PBAT. The in-situ PBAT nanofibrils facilitated the formation of PLA/PBAT hybrid shish-kebabs. The enriched shish-kebabs endowed products good strength, high toughness, outstanding heat resistance and thermostability.